PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III SD NEGERI 037 TAPUNG KECAMATAN TAPUNG - Nurjamal Nurjamal; Hendri Marhadi; Jesi Alexander Alim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrak : The background of this research is the implementation of IPA student learning outcomes Class III Elementary School 037 Tapung unsatisfactory it is known from 35 students only 18 or 51.43% that reach a predetermined school KKM is 75. Subjects in this study were students of class III SD Negeri 037 Tapung 2014/2015 the number of students 35 people consisting of 15 men and 20 women. Data collection techniques in this study consisted of observation, and documentation. While the techniques of data analysis in this study are: the activities of teachers and students, learning outcomes IPA, IPA increase in the value of learning outcomes, as well as mastery learning science students. These results indicate that the implementation of inquiry learning model can improve the activity of teachers and students at each meeting of cycle I and II in the learning process. Teacher activity at the first meeting of the first cycle is only 54.17%. Then increased at the second meeting of the first cycle as much as 8.33% be 62.50%. While at the third meeting of the second cycle of teacher activity increased again as much as 12.50% be 75% and in the fourth meeting of the second cycle increased again as much as 20.83% be 95.83%. While the activities of students at the first meeting of the first cycle the percentage is only 50%. Then at the second meeting happened an increase of 12.50% to 62.50%. In the second cycle of the third meeting of student activity increased by 12.50% to 75% and in the fourth meeting increased by 16.67% to 91.67%. Science learning outcomes completeness third grade students of SD Negeri 037 Tapung individually and classically also increased in each cycle. At the base score only 18 students who completed individually with the percentage of 51.43% classical completeness, the repeat first cycle increased to 25 students who completed individually with classical completeness percentage of 71.43%, and the repeat second cycle increased to 32 those students who completed individually with a percentage of 91.43% classical completeness. The average value of student learning outcomes also increased, where the base score is only 66.86%. Then at the first cycle increased by 7.69% to 72 and the second cycle the average value of student learning outcomes increased by 19.86% to 80.14.Keywords: inquiry learning, learning outcomes